MOTIVASI GURU DAN PRESTASI BELAJAR PESERTA DIDIK - Assyauqi, Yasid; Suarga, Suarga (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Abstract: This type of research is to study the description of teacher motivation in SMA Negeri 1 Mamasa Kab. Mamasa Prov, Sul-Bar; To find out how to learn student achievement in SMA Negeri 1 Mamasa Kab. Mamasa Prov, Sul-Bar; To find out the motivation to learn teachers about student learning achievement in SMA Negeri 1 Mamasa Kab. Mamasa Prov, Sul-Bar. The population of the study consisted of all teachers in the field of 40 succession studies in SMA Negeri 1 Mamasa Kab. Mamasa Prov, Sul-Bar. The entire population was used as the total sampling in this study. Data were analyzed using simple regression. Research Results encourage (1) An overview of teacher motivation in SMA Negeri 1 Mamasa Kab. Mamasa Prov, Sul-bar shows that the teacher motivation index scores obtained were 87.46% or included in the category of excellent teacher motivation (2) An overview of students’ learning achievements in SMA Negeri 1 Mamasa, Kab. Mamasa Prov, Sul-bar shows that the value of students’ learning achievement of 88.63% is included in the category of good student learning achievement (3) Motivation of teachers against student achievement in SMA Negeri 1 Mamasa, Kab. Mamasa Prov, Sul-Bar, this is evidenced by the significance value of 0.08 smaller when compared to α at the 0.05 significance level. The implications of research research that contains suggestions in this study are based on research findings that produce a R Square value of 0, 17 shows the ability of the independent variable in explaining the devendent variable of 17.0% is accepted at 83.0% requested by other variables not discussed in this study. This means that the teacher’s motivation variable has little effect on students’ learning achievement. Based on this, it is suggested in this study: (1) To the school that suggests doing a business that can increase teacher motivation, this motivation can be in the form of giving awards or awards to outstanding teachers; (2) To further research to add other variable variables that have not been revealed in this study.